The Relationship Of Adolescent Women's Knowledge About Maturing The Age Of Marriage On The Risk Of Early Marriage At SMPN 5 Panyabungan Kota Mandailing Natal Regency - Ester Selfia Napitupulu; Helmi Wardah Nasution (Jurnal EduHealth, 2021)
Adolescence is a transition period from childhood to adulthood, during which rapid growth occurs, including reproductive function, which influences developmental changes, both physical, mental and social roles. Early Marriage is the behavior of a person, whether male or female, when they have not yet reached true maturity (i.e. over 20 years for women and 25 years for men). The researcher's aim: to determine the relationship between young women's knowledge about maturing marriage age and the risk of early marriage at SMP Negeri 5 Panyabungan. Research method: namely a correlational method, sample size of 55 people. The instrument used was a questionnaire. The results of the analysis prove that the majority of teenagers with poor knowledge are 27 people (49%), while the minority are teenagers with good knowledge as many as 6 people (10.9%). The research results show that there is a relationship between knowledge based on age (p value = 0.021), and knowledge based on information sources (p value = 0.014). Young Women Regarding the Age of Marriage and the Risks of Early Marriage at SMP Negeri 5 Panyabungan, Mandailing Natal Regency. In conclusion, the results of the analysis prove that the majority of teenagers have poor knowledge, 27 people (49%), while the minority are teenagers with good knowledge, 6 people (10.9%).